High-strength resin and preparation method thereof
By increasing the pressure and temperature of the polymerization reaction, using RAFT chain transfer agent and reducing the use of initiators, the existing resins have been solved, and the resin preparation with high spheric grinding and long life is achieved.
Patent Information
- Application Number
- CN202510190667.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-25
AI Technical Summary
The existing styrene-type ion exchange resin has low strength and the permeability rate is not easily reached more than 95%, which leads to an increase in the crushing rate of the resin under harsh conditions such as high salt content, high osmotic pressure, and high flow rate, increasing the operating resistance, and decreasing the effluent flow rate, which in turn shortens the resin replacement cycle and increases the operating cost.
By increasing the pressure and temperature of the polymerization reaction, using RAFT chain transfer agents are used to control the molecular weight distribution of the polymer, reducing the use of initiators to avoid structural defects, and filling nitrogen deoxygenation before the polymerization reaction to scavenge the radical terminator, styrene-based resin beads with high polymerization are prepared.
It significantly improves the mechanical strength and fatigue crushing resistance of the resin, improves the spherical rate of seepage and grinding and strengthens the spherical rate of seepage and grinding, extends the service life of the resin and reduces the operating cost.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion exchange resin manufacturing, in particular to a high-strength resin and a preparation method thereof. Background Art
[0002] Ion exchange resins and adsorption resins (hereinafter collectively referred to as resins) are widely used in pure water preparation, water purification, pigment and impurity removal in the food industry, drug refining and purification, etc. due to their unique ion exchange function and polymer structure. In general industrial applications, ion exchange resins that meet the DL / T519-2004 power industry standard and relevant national standards can play their due role. The resin has a large processing capacity, high chemical stability, can be repeatedly regenerated, has a long working life, and has a low operating cost.
[0003] In order to ensure that the resin can still be used normally in relatively harsh usage scenarios such as high salt content, high osmotic pressure, and high flow rate, some companies in the resin industry have established enhanced grinding ball rate detection methods and resin fatigue test detection methods. The former refers to the GB / T12598-2001 grinding ball rate detection method, and strengthens the acid (or alkali) shock-water washing-5 alkali (or acid) shock-water washing to acid (or alkali) shock-water washing-alkali (or acid) shock-water washing for a total of 10 times, and then uses a ball mill for ball rate detection. Resins with high ball rates in enhanced grinding are more suitable for water treatment and other industrial applications, have a lower breakage rate, and have a longer service life. Generally, the ball rate of gel resin after grinding is required to be above 90%, and the ball rate of macroporous resin after grinding is required to be 90% to be qualified before leaving the factory. The enhanced infiltration and grinding ball rate is an internal control indicator of some technologically advanced resin manufacturers. It is mainly set to ensure that the resin can still be used normally under relatively harsh usage scenarios such as high salt content, high osmotic pressure, and high flow rate. At present, it has not been widely promoted for testing. The strength index of adsorption resin is implemented in accordance with ion exchange resin.
[0004] The traditional synthesis of styrene-based ion exchange resins is to first mix styrene and crosslinking agent divinylbenzene (both are called monomers) in a certain proportion, and then perform suspension polymerization to obtain crosslinked polystyrene beads, commonly known as white balls. If macroporous resins are to be prepared, appropriate inert solvents need to be added as porogens when preparing monomers. The polymerization process is to conduct free radical polymerization of styrene and divinylbenzene under the action of peroxide initiators such as benzoyl peroxide. From the basic theory of free radical polymerization, it can be seen that the free radicals generated by the decomposition of the initiator participate in the chain reaction chain initiation and chain termination of styrene polymerization. Due to the conjugation effect of the benzene ring, the activity of styrene free radicals is relatively low, and the degree of polymerization is generally around 100. The higher the concentration of initiator added, the shorter the molecular chain of polystyrene. The two olefin bonds of divinylbenzene added during the polymerization process can be polymerized in different polystyrene polymer chains, connecting two polystyrene molecular chains to form a network of body polymers. In theory, a polymer bead is a macromolecule. However, in the internal structure of the beads, the lower the degree of polymerization of the polystyrene main chain, the more breakpoints are left. The styrene-based ion exchange resin produced retains these defects. During use, the ion exchange resin needs to undergo repeated acid and alkali treatment, volume expansion and contraction, and the remaining breakpoint defects become the starting point for cracks and breakage of the resin particles.
[0005] Therefore, the existing styrene resin has low strength, and the ball rate of infiltration grinding is not easy to reach more than 95%. The ball rate of enhanced infiltration grinding is even lower. Under relatively harsh conditions of use, such as high salt content, high osmotic pressure, and high operating pressure, the resin breakage rate increases, the operating resistance increases, and the water flow rate drops significantly. These problems shorten the replacement cycle of styrene resins, increase operating costs, and sometimes even have to abandon the resin treatment plan. Summary of the invention
[0006] In order to solve the above problems of the prior art, the present invention provides a high-strength resin and a preparation method thereof, and obtains styrene resin beads with a high degree of polymerization. The mechanical strength of the synthesized anion and cation exchange resin and adsorption resin is greatly improved.
[0007] The present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing a high-strength resin, comprising the following steps: S1, dissolving a dispersant in water to obtain an aqueous phase; preparing an oil phase with a polymerizable monomer, a RAFT chain transfer agent, and a porogen; wherein the mass of the RAFT chain transfer agent is 0-0.8% of the mass of the polymerizable monomer; the polymerizable monomer is styrene and divinylbenzene, and the mass of the porogen is 0-1.5 times the mass of the polymerizable monomer; or, the polymerizable monomer is divinylbenzene, and the mass of the porogen is 1-2 times the mass of the polymerizable monomer; S2, stirring and mixing the oil phase and the water phase in a reaction container, sealing, evacuating the reaction container under stirring conditions, and then filling the reaction container with nitrogen to a pressure of 0.05-0.15 MPa; heating to a temperature of 105-150° C. and a pressure of 0.3-0.6 MPa, and performing a polymerization reaction to obtain white balls; wherein, when a porogen is added to the oil phase, the porogen in the white balls is removed; S3, when the polymerization monomers are styrene and divinylbenzene, the obtained white balls are prepared into ion exchange resin; when the polymerization monomer is divinylbenzene, the obtained white balls are prepared into adsorption resin.
[0008] Preferably, in S1, sodium chloride is also added to the aqueous phase.
[0009] Preferably, in S1, the water is deionized water.
[0010] Preferably, in S1, methylene blue is also added to the aqueous phase.
[0011] Preferably, in S1, a cross-linking agent is also added to the oil phase.
[0012] Preferably, in S2, the reaction vessel is evacuated under stirring conditions, and then nitrogen is filled into the reaction vessel to a pressure of 0.05-0.15 MPa, specifically: the reaction vessel is evacuated under stirring conditions to a pressure lower than -0.06 MPa, and then nitrogen is filled into the reaction vessel to a pressure of 0.05-0.15 MPa, and the nitrogen is evacuated to normal pressure, and the operation is repeated at least twice. After the last filling of nitrogen to a pressure of 0.05-0.15 MPa, the temperature is increased.
[0013] Preferably, in S2, after nitrogen is filled to a pressure of 0.05-0.15 MPa, the interior of the reaction container is irradiated with ultraviolet light while the temperature is raised.
[0014] Preferably, in S2, the temperature is raised to 120-150°C.
[0015] Preferably, in S3, when the polymerization monomers are styrene and divinylbenzene, the obtained white balls are prepared into ion exchange resins, specifically, the white balls are mixed with concentrated sulfuric acid and a solvent, subjected to a sulfonation reaction, and then the solvent is removed and washed to obtain a cation exchange resin; or the white balls are mixed with chloromethyl ether, swelled, and then a catalyst is added to carry out a chloromethylation reaction to obtain chlorine balls; the chlorine balls are subjected to an amination reaction with an aminating agent to obtain an anion exchange resin; When the polymerization monomer is divinylbenzene, the obtained white balls are prepared into an adsorption resin, specifically, the white balls with the porogen removed are directly used as the adsorption resin.
[0016] In a second aspect, the present invention provides a high-strength resin obtained by the preparation method as described above.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The resin preparation method of the present invention, first, by advancing the styrene-divinylbenzene copolymerization or divinylbenzene polymerization reaction carried out under ordinary normal pressure to a high pressure of 0.3-0.6MPa, the polymerization temperature can be increased like this, thereby improving the reactivity of polystyrene and styrene free radicals or divinylbenzene free radicals, and then improving the mean molecular weight of the polystyrene main chain or the polydivinylbenzene main chain in the polymer. At the same time, the pressure and temperature of the polymerization reaction are increased, the polymerization rate and the molecular weight of the polymer can be increased, the molecular weight distribution dispersity is reduced, the polymer mean molecular weight is increased, and the polymerization degree is improved. Secondly, the present invention does not add a free radical initiator, avoids the initiator from introducing an end-capping group on the main chain, and also eliminates the structural defects caused by the decomposition of the initiator to produce micro-bubbles. Again, nitrogen filling and deoxidation are performed before the polymerization reaction to remove the free radical terminator oxygen, avoid the free radical deactivation caused by dissolved oxygen, and cause the main molecular chain growth to terminate. In addition, the present invention selectively adds a reversible addition-fragmentation chain transfer (RAFT) agent. Due to the conjugation effect of the benzene ring, the free radical concentration of styrene or divinylbenzene in the polymerization reaction is high, and the termination reaction of the free radical is easy to occur, resulting in a shorter polymer molecular chain and a lower average molecular weight. The present invention can react with the long-chain free radical to form a dormant intermediate in the polymerization reaction by adding a RAFT chain transfer agent. During the reaction, the dormant intermediate and the active chain segment coexist and can be switched with each other through a dynamic reversible reaction, thereby reducing the concentration of active free radicals in the polymerization reaction, so that only a few active chains grow during the polymerization process, and finally the growth probability of each chain segment is roughly equal, thereby narrowing the molecular weight distribution range of the polymer and increasing the average molecular weight of the polymer. The average molecular weight of the final polymer is increased, the degree of polymerization is increased, and the mechanical strength and fatigue crushing resistance of the styrene resin are increased. According to the method of the present invention, the ball rate of the resin is increased by 20-60%, and the ball rate of the enhanced ball rate is increased by 30-50%, and an ion exchange resin and an adsorption resin with excellent ball rate and enhanced ball rate are obtained. The gel resin with a ball rate of more than 90% after grinding and a ball rate of 20-30% after infiltration and grinding made by the traditional process can reach a ball rate of 80% or even more than 90% after infiltration and grinding according to the process of the present invention. The first polymerization process reaches or exceeds the ball rate index of the interpenetrating white ball process of the second polymerization, and improves the qualified rate of the electrical standard DL / T519-2004. The macroporous resin with a ball rate of 60% after infiltration and grinding made by the traditional process can obtain a macroporous cation exchange resin, a macroporous anion exchange resin and a macroporous adsorption resin with a ball rate of more than 90% and an enhanced infiltration and grinding rate of more than 90% according to the process of the present invention.
[0018] Furthermore, the present invention supplements the ultraviolet light initiation means, which can further increase the polymerization degree of the polymer main chain, reduce the presence of break points and other defects in the copolymer bead molecular chain, and thus improve the mechanical strength of the resin. DETAILED DESCRIPTION
[0019] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0020] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0021] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0022] The method for preparing the high-strength resin of the present invention comprises the following steps: S1, dissolving a dispersant in water to obtain an aqueous phase; preparing an oil phase with a polymerizable monomer, a RAFT chain transfer agent, and a porogen; wherein the mass of the RAFT chain transfer agent is 0-0.8% of the mass of the polymerizable monomer; the polymerizable monomer is styrene and divinylbenzene, and the mass of the porogen is 0-1.5 times the mass of the polymerizable monomer; or, the polymerizable monomer is divinylbenzene, and the mass of the porogen is 1-2 times the mass of the polymerizable monomer; S2, stirring and mixing the oil phase and the water phase in a reaction container, sealing, evacuating the reaction container under stirring conditions, and then filling the reaction container with nitrogen to a pressure of 0.05-0.15 MPa; heating to a temperature of 105-150° C. and a pressure of 0.3-0.6 MPa, and performing a polymerization reaction to obtain white balls; wherein, when a porogen is added to the oil phase, the porogen in the white balls is removed; S3, when the polymerization monomers are styrene and divinylbenzene, the obtained white balls are prepared into ion exchange resin; when the polymerization monomer is divinylbenzene, the obtained white balls are prepared into adsorption resin.
[0023] The polymerization reaction for producing ion exchange resin and adsorption resin is usually carried out at normal pressure, and the maximum reaction temperature does not exceed 98°C. If it exceeds, the reaction will boil over and production cannot proceed normally. The preparation method of the present invention firstly increases the system pressure of the polymerization process to increase the polymerization reaction temperature to 105-150°C. The best is to increase the reaction temperature to 120-150°C, at which time the reactor pressure is about 0.30-0.60MPa. Simply increasing the pressure has almost no effect on the polymerization reaction. Increasing the pressure allows the polymerization reaction temperature to rise, which is helpful to increase the molecular weight of the polymer. Increasing the reaction temperature and pressure can increase the free radical reaction activity of styrene, and at the same time utilize thermal initiation to generate a polystyrene main chain with a high degree of polymerization; secondly, reducing the amount of initiator to 0-0.2% of the total mass of the monomer, and optimally, reducing the amount of initiator to 0, that is, not adding a free radical initiator, reducing or eliminating the presence of initiator end-capping of the polystyrene main chain, and also avoiding structural defects caused by tiny bubbles generated by the gas generated by the decomposition of the initiator; thirdly, adding a RAFT chain transfer agent to reduce the molecular weight distribution range of the polymer and increase the average molecular weight of polystyrene; further, nitrogen filling and deoxygenation before the polymerization reaction can remove the oxygen of the free radical terminator to avoid the inactivation of free radicals caused by dissolved oxygen, which causes the termination of the chain growth of the polystyrene main molecular chain.
[0024] In order to better improve the degree of polymerization of the polymer and the strength of the resin, deionized water is used in S1 of the present invention to prepare the water phase to eliminate the quenching effect of metal ions such as iron, copper, nickel, chromium, calcium, and magnesium in tap water on free radicals. The conductivity of the deionized water used in the present invention is below 10 μs / cm.
[0025] In addition, the present invention can also add 0.5%-10% analytically pure sodium chloride into the water phase to reduce the solubility of water in the oil phase, increase the interfacial tension between water and the polymerized monomer, improve the uniform dispersion effect of the oil phase, and prevent the polymerized monomer droplets from aggregating and bonding during the copolymerization process.
[0026] The present invention can also add methylene blue into the water phase to prevent the emulsion polymerization of the polymerization monomer in the water, and can also eliminate the dissolved oxygen in the water to shorten the induction period of the polymerization.
[0027] In some specific embodiments, the aqueous phase of the present invention comprises: sodium chloride, polyvinyl alcohol, sodium carboxymethyl cellulose, methylene blue and water, and the mass ratio of sodium chloride, polyvinyl alcohol, sodium carboxymethyl cellulose, methylene blue and water is: (1-10): (0.1-0.8): (0.1-0.2): (1×10 -4 -1×10 -3 ): 100. The mass ratio of oil phase to water phase is 1: (2-3).
[0028] The RAFT chain transfer agent described in the present invention is a dithioester derivative, such as benzyl dithiobenzoate, isobutyronitrile dithionaphthoate, 2-phenyl-2-propylbenzodisulfide, 2-cyanoisopropyl dithiobenzoate, dibenzyl trithiocarbonate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, more preferably benzyl dithiobenzoate and dibenzyl trithiocarbonate.
[0029] The present invention S2 specifically comprises: adding the oil phase to the water phase in the reaction container, standing, starting stirring, adjusting the stirring speed to control the oil droplet particle size, sealing, evacuating the reaction container under stirring conditions to a pressure lower than -0.06MPa, charging nitrogen to a pressure of 0.1MPa, exhausting the nitrogen to normal pressure, repeating the operation at least twice, charging nitrogen to a pressure of 0.1MPa for the last time, heating at a rate of 2-3°C / 10 minutes, when the temperature in the reaction container rises to 60-100°C, the polymerization reaction begins to initiate, releasing reaction heat, and the temperature rise rate accelerates, at this time, the external heating can be turned off according to the situation, the temperature can reach up to 120-150°C, the pressure in the reaction container can reach up to 0.6Mpa, about 0.5-2.0h later, the polymerization reaction is completely exothermic, the kettle temperature drops, and the polymerization reaction is completed after aging at 120-150°C for 2-6h to obtain white balls; wherein, when a porogen is added to the oil phase, the porogen in the white balls is removed. The process can more fully remove oxygen by repeatedly vacuuming and filling with nitrogen. Here, ordinary stirring granulation is used as an example, but it is not limited to stirring granulation. The spray granulation method is also applicable to the present invention.
[0030] Specifically, the resin of the present invention can be divided into ion exchange resin and adsorption resin, ion exchange resin can be divided into gel ion exchange resin and macroporous ion exchange resin, gel ion exchange resin can be divided into gel cation exchange resin and gel anion exchange resin; macroporous ion exchange resin can be divided into macroporous cation exchange resin and macroporous anion exchange resin.
[0031] If macroporous ion exchange resin is to be prepared, an appropriate amount of inert solvent needs to be added to the oil phase as a pore-forming agent. After the reaction is completed, the pore-forming agent is removed to obtain macroporous white balls. When preparing adsorption resin, its synthesis principle is actually the same as that of macroporous white balls of macroporous ion exchange resin. The difference is that adsorption resin generally requires a specific surface area of 200-400m 2 / g or more, it is valuable to use, but ordinary macroporous white balls do not have this requirement. Therefore, the cross-linking degree of the monomers used to prepare the adsorption resin must be above 40%, and the amount of porogen added is also relatively large.
[0032] The proportion of divinylbenzene to the total amount of polymerized monomers, i.e., the degree of crosslinking, can vary within a wide range depending on the type of resin prepared. For gel cation exchange resins or gel anion exchange resins, the degree of crosslinking is generally in the range of 4%-10%; for macroporous cation exchange resins or macroporous anion exchange resins, the degree of crosslinking is generally in the range of 5%-12%. The type and quality of the porogen used in the macroporous resin may vary depending on the type of resin; for adsorption resins, the degree of crosslinking is generally in the range of 40%-85%. The range of crosslinking degrees described here is only a commonly used range and does not limit the scope of application of the present invention.
[0033] For low cross-linking resins or porogens with more adsorbent resins, the monomer copolymerization initiation temperature is high and the polymerization reaction rate is slow. The present invention uses an ultraviolet irradiation device to photoinitiate the monomer polymerization. Of course, according to the need for reaction temperature and pressure control, the polymerization reaction of all types of resins in the present invention can use ultraviolet light initiation as a supplementary initiation method. Specifically, in S2, ultraviolet light irradiation is performed while the temperature is raised. The photoinitiated polymerization reaction will not produce end-capping groups of free radical initiators. In theory, it can also increase the degree of polymerization of the polystyrene main chain. The light initiation intensity can be adjusted in time, which can be used as a means of regulating and controlling the speed of thermal initiation reactions.
[0034] The preparation methods of each resin are introduced below.
[0035] The preparation method of the gel cation exchange resin specifically comprises: S1, dissolving a dispersant in water to obtain a water phase; mixing styrene, divinylbenzene and a RAFT chain transfer agent to obtain an oil phase; wherein the mass of the RAFT chain transfer agent is 0-0.8% of the total mass of styrene and divinylbenzene; S2, stirring and mixing the oil phase and the water phase in a reaction container, sealing, evacuating the reaction container under stirring conditions, and then filling the reaction container with nitrogen to a pressure of 0.05-0.15 MPa; heating to 105-150° C. and a pressure of 0.3-0.6 MPa, and performing a polymerization reaction to obtain white balls; S3, mixing the white balls with concentrated sulfuric acid and a solvent to carry out a sulfonation reaction, and then removing the solvent and washing to obtain a gel cation exchange resin.
[0036] In the preparation process of the gel cation exchange resin, concentrated sulfuric acid with a mass fraction of 92-98% is used, dichloroethane is used as the solvent, the mass ratio of white balls to concentrated sulfuric acid is 1: (5-7), the mass ratio of white balls to dichloroethane is 1: (0.3-0.6), the sulfonation reaction temperature is 105°C, and the reaction time is 8-12h.
[0037] The preparation method of the macroporous cation exchange resin specifically comprises: S1, dissolving a dispersant in water to obtain a water phase; mixing styrene, divinylbenzene, TAIC (triallyl isocyanate), a RAFT chain transfer agent and a porogen to obtain an oil phase; wherein the mass of the RAFT chain transfer agent is 0-0.8% of the total mass of styrene and divinylbenzene, the mass of TAIC is 1%-2% of the total mass of styrene and divinylbenzene, and the mass of the porogen is 0.5-2 times the total mass of styrene and divinylbenzene; S2, stirring and mixing the oil phase and the water phase in a reaction container, sealing the reaction container, evacuating the reaction container under stirring conditions, and then filling the reaction container with nitrogen to a pressure of 0.05-0.15 MPa; heating the reaction container to 105-150° C. and a pressure of 0.3-0.6 MPa to carry out a polymerization reaction, and removing the porogen from the obtained product to obtain a white ball; S3, mixing the white balls with concentrated sulfuric acid and a solvent to carry out a sulfonation reaction, and then removing the solvent and washing to obtain a macroporous cation exchange resin.
[0038] Among them, in the preparation method of macroporous cation exchange resin, the amount of 92%-98% concentrated sulfuric acid and ethylene dichloride is larger than that in gel cation exchange resin, the mass ratio of white ball: concentrated sulfuric acid = 1: (6-10), the mass ratio of white ball: ethylene dichloride = 1: (0.4-0.8). TAIC is a cross-linking agent, which can adjust the cross-linking bond distribution to be more uniform, which is beneficial to improve the infiltration and grinding ball rate of macroporous ion exchange resin. In the preparation method of gel and macroporous cation exchange resin, the resin is post-treated after the sulfonation reaction is completed, and the method of gradient acid dilution is carried out. On the one hand, sulfuric acid with a higher concentration can be recovered as a by-product for sale, and on the other hand, it is also conducive to the stable control of the resin quality. The specific method is to filter out the mother liquor after the temperature in the kettle drops below 30°C, and dilute it step by step with 65%-5% multi-grade sulfuric acid, and gradient acid with each grade concentration reduced by 5%-10%. Each dilution is stirred for 30-60 minutes, and the temperature is controlled below 40°C during the dilution. After the 5% sulfuric acid is added, it is diluted with tap water. The specific gravity of the filtered dilute sulfuric acid is generally less than 1.02 after the dilution is completed. Then wash it with water twice, add the required amount of sodium hydroxide solution for transformation, wash it with a large amount of water until it is neutral, and discharge it.
[0039] The preparation method of the gel anion exchange resin specifically comprises: S1, dissolving a dispersant in water to obtain a water phase; mixing styrene, divinylbenzene and a RAFT chain transfer agent to obtain an oil phase; wherein the mass of the RAFT chain transfer agent is 0-0.8% of the total mass of styrene and divinylbenzene; S2, stirring and mixing the oil phase and the water phase in a reaction container, sealing, evacuating the reaction container under stirring conditions, and then filling the reaction container with nitrogen to a pressure of 0.05-0.15 MPa; heating to 105-150° C. and a pressure of 0.3-0.6 MPa, and performing a polymerization reaction to obtain white balls; S3, mixing the white ball with chloromethyl ether, swelling it, and then adding a catalyst to carry out chloromethylation reaction to obtain chlorine ball; carrying out an amination reaction of the chlorine ball with an amination reagent to obtain a gel anion exchange resin.
[0040] The preparation method of the macroporous anion exchange resin specifically comprises: S1, dissolving a dispersant in water to obtain an aqueous phase; mixing styrene, divinylbenzene, TAIC, a RAFT chain transfer agent and a porogen to obtain an oil phase; wherein the mass of the RAFT chain transfer agent is 0-0.8% of the total mass of styrene and divinylbenzene, the mass of TAIC is 1%-2% of the total mass of styrene and divinylbenzene, and the mass of the porogen is 0.5-2 times the total mass of styrene and divinylbenzene; S2, stirring and mixing the oil phase and the water phase in a reaction container, sealing the reaction container, evacuating the reaction container under stirring conditions, and then filling the reaction container with nitrogen to a pressure of 0.05-0.15 MPa; heating the reaction container to 105-150° C. and a pressure of 0.3-0.6 MPa to carry out a polymerization reaction, and removing the porogen from the obtained product to obtain a white ball; S3, mixing the white ball with chloromethyl ether, swelling it, and then adding a catalyst to carry out chloromethylation reaction to obtain chlorine ball; carrying out an amination reaction of the chlorine ball with an amination reagent to obtain a macroporous anion exchange resin.
[0041] In the preparation method of the gel anion exchange resin, S3 specifically includes: adding chloromethyl ether to the white ball, stirring at room temperature for 2 hours for pre-expansion, then adding ferric chloride and heating to 43°C and keeping warm for 20 hours, and filtering out the mother liquor after the reaction is completed; washing the obtained gel chloride ball twice with methylal, and then performing an amination reaction; when performing the amination reaction, dripping the trimethylamine aqueous solution into the methylal suspension of the gel chloride ball, controlling the temperature below 30°C during the dripping, and keeping warm at 32°C for 4-6 hours after the dripping is completed.
[0042] In the preparation method of the macroporous anion exchange resin, S3 specifically includes: adding chloromethyl ether to the white balls, stirring at room temperature for 2 hours for pre-expansion, then adding ferric chloride and heating to 43°C for 20 hours, filtering out the mother liquor after the reaction is completed; washing the obtained macroporous chlorine balls with water, recovering the organic components, and finally washing with a large amount of water until neutral, and performing an amination reaction; when performing the amination reaction, adding a trimethylamine aqueous solution dropwise to the water suspension of the macroporous chlorine balls, controlling the temperature below 30°C during the addition, and keeping the temperature at 32°C for 4-6 hours after the addition is completed.
[0043] If a weakly basic anion exchange resin is prepared, the amination reaction requires replacing the above trimethylamine aqueous solution with a dimethylamine aqueous solution, and the reaction temperature is also required to be slightly higher.
[0044] The methods of chloromethylation vary greatly, and the present invention does not make any special requirements, except that the chlorine content of the gel chlorine spheres is greater than 16.5% and the chlorine content of the macroporous chlorine spheres is greater than 17.5%.
[0045] The processes of chloromethylation and amination reaction vary greatly among manufacturers, and the present invention does not make any special requirements. As long as the index requirements of DL / T519-93 can be met, the ball rate of the gel strong basic anion exchange resin after grinding is above 90%, and the ball rate of the macroporous strong basic anion resin and the macroporous weak basic anion resin after infiltration grinding is above 90%, such chloromethylation and amination processes can be used in the present invention.
[0046] The preparation method of the adsorption resin specifically comprises: S1, dissolving a dispersant in water to obtain an aqueous phase; mixing divinylbenzene, a RAFT chain transfer agent and a porogen to obtain an oil phase; wherein the mass of the RAFT chain transfer agent is 0-0.8% of the mass of divinylbenzene, and the mass of the porogen is 1-2 times the mass of divinylbenzene; S2, stirring and mixing the oil phase and the water phase in a reaction container, sealing the reaction container, evacuating the reaction container under stirring conditions, and then filling the reaction container with nitrogen to a pressure of 0.05-0.15 MPa; heating to 105-150°C and a pressure of 0.3-0.6 MPa to carry out a polymerization reaction, removing the porogen from the obtained product, and obtaining white balls, which are the adsorption resin.
[0047] The method for removing the porogen of the present invention can be: removing the porogen by steam distillation or solvent extraction, leaving permanent pores, washing, discharging, and obtaining an adsorption resin with a very high specific surface area, which can be used as an adsorbent.
[0048] Example 1 Preparation of high-strength gel white balls: Add 1000mL pure water, 30g sodium chloride, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (mass content 0.1%) to a 2000mL autoclave and stir evenly to obtain an aqueous phase. Mix 450g styrene, 55.6g divinylbenzene (mass content 63.0%), and 2.5g benzyl dithiobenzoate in a beaker to obtain an oil phase, in which styrene and divinylbenzene have been freed from inhibitors. Pour the mixed oil phase into the aqueous phase, let it stand, turn on the stirring and adjust the speed to adjust the oil droplet size within the required range. Vacuum the autoclave under stirring until the pressure is lower than -0.06MPa, fill it with nitrogen to 0.1MPa, exhaust the nitrogen to near normal pressure, and then perform two more vacuuming and nitrogen filling and exhausting operations. After the last filling of 0.1MPa nitrogen, it is stored in the reactor. Then the temperature is raised to react. During the heating process, the heating rate is not less than 2℃ / 10 minutes. When the temperature rises to about 80℃, polymerization heat begins to be generated. The temperature continues to rise to about 90℃, and the polymerization heat is released, and the temperature rises faster. At this time, the heating power is turned off, and the kettle temperature continues to rise to 120℃. The pressure in the kettle is about 0.3MPa. When the kettle temperature stabilizes or begins to drop, the heating power is turned on, and the reaction is kept at 120℃ for 6 hours. After the reaction is completed, wait for the temperature to drop to room temperature, wash the white balls with water, and dry them for use.
[0049] Example 1.1 Preparation of gel strong acid cation exchange resin: weigh 100g of the gel white ball of Example 1 in a 1000mL dry reactor, add 550g of 92% concentrated sulfuric acid and 48g of dichloroethane, heat to 70℃ and keep warm for 2h, 80℃ and keep warm for 3h, 90℃ and keep warm for 3h, 95℃ and keep warm for 2h, heat to 105℃ and keep warm for 1h. The reaction is carried out under normal pressure, and dichloroethane is recovered by the distillation system while heating. After the insulation at 105℃ is completed, reduce the pressure, remove the dichloroethane remaining in the resin, and cool down. After the temperature drops to 30℃, dilute it step by step with 65%, 55%, 45%, 35%, 25%, 15%, and 5% gradient acid. After the dilution is completed, add water to wash until the specific gravity of the dilute sulfuric acid flowing out is less than 1.02, add water twice, add alkali to adjust the pH to 10, stabilize for 0.5h, after the pH remains unchanged, wash with a large amount of water until neutral, and discharge.
[0050] Resin indicators: sodium type exchange capacity 4.56mmol / gd (millimoles / g dry resin), water content 49.20%, ball rate after grinding 99%, ball rate after infiltration grinding 99%, and ball rate after enhanced infiltration grinding 95%.
[0051] Example 1.2 Preparation of gel strong basic anion exchange resin: weigh 100g of the gel white ball of Example 1 above into a 1000mL dry reactor, add 400mL of chloromethyl ether and stir to expand for 2h, add 30g of ferric chloride, heat to 43℃ and keep warm for 20h, filter out the mother liquor after the reaction is completed, add methylal to wash the ball twice, the first time can be washed with the second methylal recovered last time, and filter out the second methylal added. Add new methylal and stir to expand at room temperature for 2h, the amount added is based on the chlorine ball can be fully stirred, and add about 300mL of trimethylamine aqueous solution with a constant pressure funnel, during which the temperature is controlled below 30℃ and the pH value is greater than 9.0. If the mother liquor sample pH is lower than 9.0, it is necessary to add an appropriate amount of trimethylamine aqueous solution. After the addition is completed, keep warm at 32℃ for 6h. After the reaction is completed, filter out the mother liquor, add salt water and water for washing, and finally add 1mol / L hydrochloric acid and stir until the pH is 4.0, wash with water to neutrality, and discharge.
[0052] Resin indicators: Chlorine type exchange capacity 3.73mmol / gd, water content 46.81%, ball rate after grinding 98%, ball rate after infiltration grinding 98%, and ball rate after enhanced infiltration grinding 95%.
[0053] The obtained resin can be combined with the gel strong acid cation exchange resin of Example 1.1 to meet the use occasions of high osmotic pressure such as high salt concentration and high sugar concentration and the use occasions of high flow rate moving bed and other use occasions that have high requirements on the mechanical strength of the resin. For example, for 30% xylitol desalination, after 3 cycles of use, the breakage rate was only 1.4%, and the resin strength met the requirements for practical application.
[0054] Comparative Example 1 Preparation of gel white balls: Add 1000mL pure water, 30g sodium chloride, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (mass content 0.1%) to a 2000mL atmospheric pressure reactor and stir evenly to obtain an aqueous phase. Mix 450g styrene, 55.6g divinylbenzene (mass content 63.0%), 4.0g benzoyl peroxide, and 2.5g benzyl dithiobenzoate in a beaker to obtain an oil phase, in which styrene and divinylbenzene have been freed from inhibitors. Pour the mixed oil phase into the water phase, let it stand, start stirring and adjust the speed to adjust the oil droplet size within the required range. Then heat to 80°C, keep warm for 3h, heat to 90°C and keep warm for 3h, and finally heat to 98°C and keep warm for 6h to complete the polymerization reaction. After the reaction is completed, wait for the temperature to drop to room temperature, wash the white balls with water, and dry them for use.
[0055] The preparation method of the gel strong acid cation exchange resin is the same as that of Example 1.1, except that the white balls prepared in Comparative Example 1 are used to replace the gel white balls in Example 1. The indexes of the prepared gel cation exchange resin are as follows: sodium type exchange capacity 4.52mmol / gd, water content 48.61%, ball rate after grinding 91%, ball rate after infiltration grinding 56%, and ball rate after enhanced infiltration grinding 35%.
[0056] The preparation method of the gel strong basic anion exchange resin is the same as that of Example 1.2, except that the white balls prepared in Comparative Example 1 are used to replace the gel white balls in Example 1. The indexes of the prepared gel anion exchange resin are as follows: Resin index: chloride type exchange capacity 3.76mmol / gd, water content 46.11%, ball rate after grinding 93%, ball rate after infiltration grinding 52%, and ball rate after enhanced infiltration grinding 31%.
[0057] According to the conventional process, the gel strong acid cation exchange resin and gel strong basic anion exchange resin prepared in Comparative Example 1, although the ball rate after grinding can meet the requirements of DL / T519-93 and other standards, the ball rate after osmotic grinding cannot meet the requirements of DL / T519-2004. The resin can be used normally under the condition of preparing softened water or pure water from tap water, but under high osmotic pressure conditions, such as 30% xylitol desalination, the breakage rate is more than 50% after 3 cycles, and it cannot be put into practical use. Under the same working conditions, the resins of Examples 1.1 and 1.2 can be used normally, and the annual breakage rate is less than 5%.
[0058] Example 2 Preparation of high-strength gel white balls: Add 1000mL tap water, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (mass content 0.1%) to a 2000mL autoclave and stir evenly to obtain an aqueous phase. Mix 450g styrene, 55.6g divinylbenzene (mass content 63.0%), and 2.5g benzyl dithiobenzoate in a beaker to obtain an oil phase, in which styrene and divinylbenzene have been freed from inhibitors. Pour the mixed oil phase into the aqueous phase, let it stand, turn on the stirring and adjust the speed to adjust the oil droplet size within the required range. Vacuum the autoclave under stirring until the pressure is lower than -0.06MPa, fill it with nitrogen to 0.1MPa, exhaust the nitrogen to near normal pressure, and then perform two more vacuuming and nitrogen filling and exhausting operations. After the last filling of 0.1MPa nitrogen, it is stored in the reactor. Then the temperature is raised to react. During the heating process, the heating rate is not less than 2℃ / 10 minutes. When the temperature rises to about 80℃, polymerization heat begins to be generated. The temperature continues to rise to about 90℃, and the polymerization heat is released, and the temperature rises faster. At this time, the heating power is turned off, and the kettle temperature continues to rise to 120℃. The pressure in the kettle is about 0.3MPa. When the kettle temperature stabilizes or begins to drop, the heating power is turned on, and the reaction is kept at 120℃ for 6 hours. After the reaction is completed, wait for the temperature to drop to room temperature, wash the white balls with water, and dry them for use.
[0059] The preparation method of the gel strong acid cation exchange resin is the same as that of Example 1.1, except that the white balls prepared in Example 2 are used to replace the gel white balls in Example 1. The indexes of the prepared gel cation exchange resin are as follows: sodium type exchange capacity 4.55 mmol / gd, water content 49.51%, ball rate after grinding 99%, ball rate after infiltration grinding 96%, and ball rate after enhanced infiltration grinding 91%.
[0060] The preparation method of the gel strong basic anion exchange resin is the same as that of Example 1.2, except that the white balls prepared in Example 2 are used to replace the gel white balls in Example 1. The indexes of the prepared gel anion exchange resin are as follows: Resin index: chloride type exchange capacity 3.76mmol / gd, water content 47.53%, ball rate after grinding 98%, ball rate after infiltration grinding 94%, and ball rate after enhanced infiltration grinding 90%.
[0061] In Example 2, tap water was used as the aqueous phase without adding salt, and the balling rate and enhanced balling rate of osmotic grinding were lower than those of Example 1, but still above 90%. It was used for 30% xylitol desalination for 3 cycles, and the crushing rate was 7%.
[0062] Example 3 Preparation of high-strength macroporous strong acid white balls: 1000mL pure water, 20g sodium chloride, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, 1.0mL methylene blue (mass content 0.1%) are added to a 2000mL autoclave, stirred evenly to form a water phase, and heated to 60°C for use. 87.5g of chopped solid wax is heated to 80°C to melt, and an oil phase consisting of 296.5g styrene and 50g divinylbenzene (mass content 63%), 0.8g dibenzyl trithiocarbonate, and 3.5g TAIC (triallyl isocyanate) is added. Styrene and divinylbenzene have been freed of inhibitors, and mixed evenly at about 60°C to form an oil phase. The oil phase is added to the water phase, allowed to stand, and stirred to adjust the oil droplet size to the required range. Under stirring, vacuum the kettle until the pressure inside is lower than -0.06MPa, fill with nitrogen to 0.1MPa, exhaust the nitrogen to near normal pressure, and then vacuumize and fill with nitrogen twice, and exhaust nitrogen. Finally, 0.1MPa of nitrogen is retained in the reactor. Then start heating. When the temperature rises to 80℃, polymerization heat begins to be released, and then the temperature rises to about 90℃. The temperature rises rapidly. Adjust the heating rate according to the situation. Keep the heating rate not less than 2℃ / 10 minutes during the heating process, and do not perform constant temperature insulation operation. After the kettle temperature rises to 120℃, keep it at 120℃ for 6h, and the pressure in the kettle is about 0.3Mpa, and the polymerization reaction is completed. After the reaction is completed, wait for the temperature to drop to room temperature, wash the white balls with water and dry them, extract with toluene 6 times, heat up to 60℃ and keep them for about 1h each time, filter the toluene while hot, and then add new toluene for extraction. After the last round of toluene extraction is completed, the toluene is recovered by filtration, and water is added to azeotropically recover the toluene absorbed in the white balls. The temperature is above 98°C, and no oil droplets are distilled out. The extraction is completed, the large-pore white balls are filtered out, and dried for later use.
[0063] Preparation of macroporous strongly acidic cation exchange resin: Weigh 100g of macroporous white balls prepared in Example 3 into a 1000mL dry reactor, add 800g of 92% concentrated sulfuric acid and 76g of dichloroethane, heat to 80°C and keep warm for 2h, heat to 85°C and keep warm for 3h, heat to 90°C and keep warm for 3h, heat to 95°C and keep warm for 2h, heat to 115°C and keep warm for 2h. The heating and insulation reactions are always carried out under normal pressure, and the distilled dichloroethane is recovered by the distillation system. After the reaction at 115°C is completed, the dichloroethane is recovered under reduced pressure. Cool down, and when the temperature drops to 30°C, dilute the feed solution step by step with 65%, 55%, 45%, 35%, 25%, 15%, and 5% gradient acids, and finally add tap water to dilute until the effluent has a specific gravity of less than 1.02, then add water to wash twice, add alkali to adjust the pH to 11, stabilize for 0.5h, and after the pH remains unchanged, wash with a large amount of water until neutral, and discharge.
[0064] Resin indicators: sodium type exchange capacity 4.38mmol / gd, water content 51.22%, infiltration and grinding ball rate 98.5%, enhanced infiltration and grinding ball rate 96%.
[0065] Comparative Example 3 Preparation of traditional macroporous strong acid resin white balls: 1000mL pure water, 20g sodium chloride, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, 1.0mL methylene blue (content 0.1%) are added to a 2000mL three-necked flask, stirred evenly to form a water phase, and heated to 60°C for use. 87.5g of chopped solid wax is heated to 80°C to melt, and an oil phase consisting of 296.5g styrene and 50g divinylbenzene (content 63%), 0.8g dibenzyl trithiocarbonate, and 3.5g TAIC (triallyl triisocyanate) is added. Styrene and divinylbenzene have been freed of inhibitors, mixed evenly at about 60°C to form an oil phase, and finally 3.5g benzoyl peroxide is added. After adding benzoyl peroxide and stirring evenly, the oil phase is added to the water phase in the shortest possible time, and the mixture is allowed to stand. Stirring is turned on to adjust the oil droplet size to the required range. Heat up, when the temperature rises to 80℃, keep it for 3h, heat up to 90℃, keep it for 3h, heat up to 95-98℃, keep it for 6h, and complete the polymerization reaction. After the reaction is over, wait for the temperature to drop to room temperature, wash the white balls with water and dry them, extract with toluene 6 times, heat up to 60℃ and keep it for about 1h each time, filter the toluene while it is hot, and add new toluene for extraction. After the last toluene extraction is completed, filter and recover the toluene, add water to azeotropically recover the toluene absorbed in the white balls, heat to above 98℃, distill without oil droplets, extract and filter out the white balls, dry them for use.
[0066] The preparation process of the macroporous cation exchange resin is the same as that of Example 3, except that the ordinary white balls of Comparative Example 3 are used to replace the high-strength white balls of Example 3. The obtained resin has the following indicators: sodium type exchange capacity 4.39 mmol / gd, water content 52.13%, infiltration grinding ball rate 93.2%, and enhanced infiltration grinding ball rate 46%.
[0067] The synthesized macroporous strong acid cationic resin has a grinding roundness that meets the requirements of DL / T519-2004, but its enhanced grinding roundness is relatively low and cannot be used in high osmotic pressure, high flow rate and other applications that require high mechanical strength of the resin.
[0068] Example 4 Preparation of macroporous strong base anion resin high-strength white ball: Add 1000mL pure water, 30g sodium chloride, 8g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, 1.0mL methylene blue (content 0.1%) to a 2000mL autoclave and stir evenly. Add 318.5g styrene, 34.3g divinylbenzene (content 63.0%), 7.2g TAIC, 1.0g benzyl dithiobenzoate, 144g liquid wax, mix evenly in a beaker, styrene and divinylbenzene have been free of inhibitors. Pour the mixed oil phase into the water phase, let it stand, turn on the stirring and adjust the speed, and adjust the particle size within the required range. Vacuum the autoclave under stirring until the pressure is lower than -0.06MPa, fill with nitrogen to 0.1MPa, evacuate the nitrogen to near normal pressure, and then perform two more vacuuming and nitrogen filling and nitrogen exhaust operations. After the last filling of 0.1MPa nitrogen, it is stored in the reactor. After deoxygenation, the temperature is raised to react. When the temperature rises to 80°C, polymerization heat begins to be generated. The temperature continues to rise to about 90°C, and a large amount of polymerization heat is released. During the heating process, the heating rate is maintained at 2-3°C / 10 minutes, and no constant temperature insulation operation is performed. After the kettle temperature continues to rise to 120°C, the pressure in the kettle is about 0.3MPa, and the reaction is kept at 120°C for 6h. After the reaction is completed, wait for the temperature to drop to room temperature, wash the white balls with water and then dry them. Extract with toluene 6 times, each time heating to 60°C and keeping the temperature for about 1h, filter the toluene while it is hot, and then add new toluene for extraction. After the last toluene extraction is completed, filter and recover the toluene, add water to azeotropically recover the toluene absorbed in the white balls, and distill to above 98°C without oil droplets. The extraction is completed, filter out the white balls, and dry them for use.
[0069] Preparation of macroporous strong basic anion exchange resin: Weigh 100g of macroporous white balls of Example 4 in a 1000mL dry reactor, add 500mL of chloromethyl ether and stir to expand for 2h, add 30g of anhydrous ferric chloride, heat to 43°C and keep warm for 20h, take samples, and measure the chlorine content to be more than 17.5% for qualified. If it is unqualified, add chloromethyl ether and anhydrous ferric chloride in appropriate amounts. After the chlorine content is qualified, filter the mother liquor, add water to wash and recover the organic components to minimize COD emissions. Finally, wash with a large amount of water until neutral, drain, add appropriate amount of water until the chlorine ball can be fully stirred, and add about 300mL of trimethylamine aqueous solution until the mother liquor sampling pH value is greater than 9, and stabilize for 2h without decreasing, indicating that the amination reaction is complete. Sampling and measuring the strong base exchange capacity greater than 3.7mmol / gd is qualified. After the delivery volume is qualified, the mother liquor is filtered, washed with a large amount of water until it is nearly neutral, and an appropriate amount of hydrochloric acid is added to make the pH less than 2, and stabilize it for more than 1 hour, washed with a large amount of water, and discharged.
[0070] The resin performance indicators are as follows: chlorine type exchange capacity 3.75mmol / gd, water content 58.39%, infiltration and grinding ball rate 98.7%, enhanced infiltration and grinding ball rate 96.2%.
[0071] Comparative Example 4 Preparation of traditional macroporous strong base anionic resin white balls: Add 1000mL pure water, 30g sodium chloride, 8g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (content 0.1%) to a 2000mL three-necked flask and stir evenly. Mix 318.5g styrene, 34.3g divinylbenzene (content 63.0%), and 7.2g TAIC in a beaker, add 3.6g benzoyl peroxide and 1.0g benzyl dithiobenzoate, stir evenly, add 144g liquid wax, stir evenly, and form the oil phase. Both styrene and divinylbenzene have been freed of inhibitors. Pour the mixed oil phase into the water phase, let it stand, turn on the stirring and adjust the speed to adjust the particle size within the required range. Start heating reaction, keep warm for 3 hours when the temperature rises to 80℃, at this time, polymerization heat is released, continue to heat up to 90℃ and keep warm for 3 hours, then heat up to 95-98℃ and keep warm for 6 hours. After the reaction is over, wait for the temperature to drop to room temperature, wash the white balls with water and dry them. Extract with toluene 6 times, heat up to 60℃ and keep warm for about 1 hour each time, filter the toluene while it is hot, and then add new toluene for extraction. After the last toluene extraction is completed, filter and recover the toluene, add water to azeotropically recover the toluene absorbed in the white balls, and distill to above 98℃ without oil droplets. After the extraction is completed, filter out the white balls and dry them for use.
[0072] The process of chloromethylation and amination is the same as that of Example 4, only the conventional white balls of Comparative Example 4 are used to replace the high-strength white balls of Example 4, and the performance indicators of the prepared resin are as follows: chlorine type exchange capacity 3.73mmol / gd, water content 58.65%, infiltration grinding ball rate 91.7%, and enhanced infiltration grinding ball rate 52.3%. It can be seen that the enhanced infiltration grinding ball rate is lower.
[0073] Example 5 Preparation of macroporous weak base anionic resin white ball: Add 1000mL pure water, 40g sodium chloride, 8g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, 1.0mL methylene blue (content 0.1%) to a 2000mL autoclave and stir evenly. Add 72g solid wax to 72g liquid wax, heat to 80℃, stir evenly and fully dissolve. Mix 318.5g styrene, 34.3g divinylbenzene (content 63.0%), 7.2g TAIC, and 1.5g benzyl dithiobenzoate in a beaker, add to the porogen composed of the above solid wax and liquid wax, stir evenly at 60℃ to form an oil phase. Both styrene and divinylbenzene have been freed from inhibitors. Pour the mixed oil phase into the water phase, let it stand, turn on the stirring and adjust the speed to adjust the particle size within the required range. Under stirring, vacuumize until the pressure in the kettle is lower than -0.06MPa, fill with nitrogen to 0.1MPa, exhaust nitrogen to near normal pressure, and then vacuumize and fill with nitrogen and exhaust nitrogen twice. After the last filling with 0.1MPa nitrogen, it is kept in the reactor. After deoxygenation, the temperature is raised to 80℃, polymerization heat begins to be generated, and the temperature is continued to rise to about 90℃, and the heat release rate is accelerated. During the heating process, the heating rate is kept not less than 2-3℃ / 10 minutes, and the constant temperature insulation operation is not performed. After the kettle temperature continues to rise to 120℃, the pressure in the kettle is about 0.3MPa, and the reaction is kept at 120℃ for 6h. After the reaction is completed, wait until the temperature drops to room temperature, wash the white balls with water and dry them. Extract with toluene 6 times, each time heating to 60℃ and keeping warm for about 1h, filter the toluene while hot, and then add new toluene for extraction. After the last round of toluene extraction is completed, the toluene is recovered by filtration, and water is added to azeotropically recover the toluene absorbed in the white balls. The temperature is above 98°C and no oil droplets are distilled out. The extraction is completed, the white balls are filtered out, and dried for later use.
[0074] Preparation of macroporous weakly basic anion exchange resin: Weigh 100g of the macroporous white ball of Example 5 in a 1000mL dry reactor, add 500mL of chloromethyl ether, stir and expand for 2h, add 30g of anhydrous ferric chloride, heat to 43°C and keep warm for 20h, take samples, and measure the chlorine content to be more than 17.5% for qualified. If it is unqualified, add appropriate amounts of chloromethyl ether and anhydrous ferric chloride. After the chlorine content is qualified, filter the mother liquor, add water to wash and recover the organic components to minimize COD emissions. Finally, wash with a large amount of water until neutral and drain. Transfer the chlorine ball to a pressure tank with water, filter to remove water, add appropriate amount of methylal to immerse the chlorine ball, stir evenly, and expand for 2h. Recover methylal by suction filtration, add 400mL of 40% dimethylamine aqueous solution into the pressure tank, seal the pressure tank immediately, keep the reaction at 70℃ for 20h, take samples to measure the weak base exchange capacity greater than 4.8mmol / gd, and it is qualified. If it is unqualified, filter the mother liquor, add appropriate dimethylamine, heat it to 70℃ again, keep the reaction for 20h, until the exchange capacity is qualified. Cool down, recover the dimethylamine mother liquor by suction filtration, wash with a large amount of water until neutral, and discharge.
[0075] The resin performance indicators are as follows: exchange capacity 4.98mmol / gd, water content 56.61%, infiltration and grinding ball rate 98.6%, enhanced infiltration and grinding ball rate 97.2%.
[0076] Comparative Example 5 Preparation of traditional macroporous white balls: Add 1000mL pure water, 40g sodium chloride, 8g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (mass content 0.1%) to a 2000mL three-necked flask, stir evenly, and obtain a water phase. Add 72g solid wax to 72g liquid wax, heat to 80°C, stir evenly, and fully dissolve. Mix 318.5g styrene, 34.3g divinylbenzene (mass content 63.0%), 7.2g TAIC, and 1.5g benzyl dithiobenzoate in a beaker, add to the porogen composed of the above solid wax and liquid wax, and finally add 3.6g benzoyl peroxide, stir evenly, and form an oil phase. Both styrene and divinylbenzene have been freed from inhibitors. Pour the mixed oil phase into the water phase, let it stand, turn on the stirring and adjust the speed, and adjust the oil droplet size within the required range. Start heating up. When the temperature reaches 80℃, keep it warm for 3h. At this time, polymerization heat is generated. Continue to heat up to 90℃, keep it warm for 3h, and then heat up to 98℃ and keep it warm for 6h. After the reaction is over, wait for the temperature to drop to room temperature, wash the white balls with water and dry them. Extract with toluene 6 times, heat up to 60℃ and keep it warm for about 1h each time, filter the toluene while it is hot, and then add new toluene to extract. After the last toluene extraction is completed, filter and recover the toluene, add water to azeotropically recover the toluene absorbed in the white balls, and distill to above 98℃ without oil droplets. The extraction is over, filter out the macroporous white balls, and dry them for use.
[0077] The chloromethylation and amination reactions of the conventional macroporous weakly basic anion exchange resin are the same as those in Example 5, except that the macroporous white balls prepared in Comparative Example 5 are used instead of the resin white balls prepared in Example 5.
[0078] The performance indicators of the prepared resin are as follows: exchange capacity 4.85mmol / gd, water content 56.91%, infiltration grinding ball rate 95.3%, enhanced infiltration grinding ball rate 51.6%. The enhanced infiltration grinding ball rate of the obtained resin is relatively low.
[0079] Example 6 Preparation of macroporous adsorption resin: 1000mL pure water, 60g sodium chloride, 8g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, 1.0mL methylene blue (content 0.1%) are added to a 2000mL autoclave and stirred to form an aqueous phase. 168g 81.3% divinylbenzene is added to 336g toluene and stirred to form an oil phase. The oil phase is added to the water phase, allowed to stand, stirring is turned on and the speed is adjusted to adjust the oil droplet size within the required range. Under stirring, vacuum is evacuated until the pressure in the autoclave is lower than -0.06MPa, nitrogen is filled to 0.1MPa, and nitrogen is emptied to near normal pressure. Vacuum and nitrogen filling and exhaust operations are performed twice. After the last filling of 0.1MPa nitrogen, it is stored in the reactor. Then the temperature begins to rise. When the temperature rises to about 85°C, polymerization heat begins to be generated. The temperature continues to rise to about 95°C, and the heat release rate is accelerated. During the heating process, the heating rate is maintained at not less than 2°C / 10 minutes, and no constant temperature insulation operation is performed. After continuing to heat to 150°C, the pressure in the kettle is about 0.6MPa, and the reaction is kept at 150°C for 3 hours. After the reaction is completed, the temperature is lowered, the white ball is transferred to the extraction column, and water vapor at about 110°C is passed through to distill and recover toluene. After no toluene flows out, continue to pass steam for about 2 hours to completely remove the residual toluene. Cool down, wash with water, add methanol to soak for 2 hours, and filter to recover methanol. Wash with a large amount of water to remove the residual methanol to obtain a macroporous adsorption resin.
[0080] The resin performance indicators are as follows: specific surface area 862.5m 2 / gd (square meters / g. dry resin), water content 58.29%, ball rate after grinding 95.2%, enhanced infiltration grinding ball rate 90.8%. The ball rate of the resin without chain transfer agent in enhanced infiltration grinding is lower than 95%, but compared with the conventional method, the strength of the prepared resin is also significantly improved. Since the macroporous adsorption resin does not carry acid and base functional groups, the expansion rate is very low during acid and alkali treatment, and the ball rate after grinding is equivalent to the ball rate of infiltration grinding and enhanced infiltration grinding, so only the ball rate after grinding and enhanced infiltration grinding were tested.
[0081] Comparative Example 6 Preparation of traditional macroporous adsorption resin white balls and resin: Add 1000mL pure water, 60g sodium chloride, 8g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, 1.0mL methylene blue (content 0.1%) to a 2000mL three-necked flask and stir evenly. Add 168g divinylbenzene (content 81.3%) to 336g toluene, stir evenly, add 1.7g benzoyl peroxide, stir evenly to form the oil phase. Add the oil phase to the water phase, let it stand, turn on the stirring and adjust the speed, and adjust the particle size within the required range. Heat to 80℃, keep warm for 3h, heat to 85℃, keep warm for 3h, heat to 92℃, keep warm for 6h. Due to the azeotropic effect of toluene and water, the maximum temperature can only be raised to 92℃. If the temperature is higher than 92℃, foam will continue to emerge from the bottle mouth, and the reaction cannot proceed normally. After the reaction is finished, the temperature is lowered, and the white ball is transferred to the extraction column. Water vapor at about 110°C is introduced to distill and recover toluene. After no toluene flows out, the steam is continued for about 2 hours to completely remove the residual toluene. The temperature is lowered, washed with water, and methanol is added to soak for 2 hours, and the methanol is recovered by filtration. The residual methanol is removed by washing with a large amount of water to obtain a macroporous adsorption resin.
[0082] The resin performance indicators are as follows: specific surface area 882.9m 2 / gd (square meters / g. dry resin), water content 58.55%, ball rate after grinding 51.2%, enhanced infiltration grinding ball rate 41.3%. The ball rate after grinding and enhanced infiltration grinding of the resin are both low, which is significantly different from the high-strength resin prepared in Example 6.
[0083] Example 7 Preparation of high-strength gel resin 001×4 white balls: 1000mL pure water, 100g sodium chloride, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (content 0.1%) were added to a 2000mL autoclave and stirred evenly to form an aqueous phase. 468.3g styrene, 31.7g divinylbenzene (mass content 63.0%), and 2.0g dibenzyl trithiocarbonate were mixed evenly in a beaker to form an oil phase; wherein styrene and divinylbenzene have been freed from inhibitors. The mixed oil phase was poured into the water phase, allowed to stand, and the stirring was turned on to adjust the speed to adjust the oil droplet size within the required range. Under stirring, vacuum was evacuated until the pressure in the autoclave was lower than -0.06MPa, nitrogen was charged to 0.1MPa, and nitrogen was emptied to near normal pressure, and vacuum was evacuated and nitrogen was charged and discharged twice. After the last charge of 0.1MPa nitrogen, it was stored in the reactor. Then the temperature is raised to react. During the heating process, the heating rate is not less than 2℃ / 10 minutes. When the temperature rises to about 80℃, polymerization heat begins to be generated. The temperature continues to rise to 90℃, a large amount of polymerization heat is released, and the temperature rises rapidly. At this time, the heating power is turned off, and the kettle temperature continues to rise to 140℃. The pressure in the kettle is 0.5MPa. When the kettle temperature stabilizes or begins to drop, the heating power is turned on and the reaction is kept at 150℃ for 6 hours. After the reaction is completed, wait for the temperature to drop to room temperature, wash the white balls with water, and dry them for use.
[0084] The preparation of gel cation exchange resin was carried out with reference to Example 1.1, and the resin indexes were as follows: sodium type exchange capacity 4.59mmol / gd, water content 56.34%, ball rate after grinding 98%, ball rate after infiltration grinding 91%, and ball rate after enhanced infiltration grinding 82.5%. Since the crosslinking degree was lower than that of the 001×7 resin in Example 1.1, the resin water content was high, and the ball rate after enhanced infiltration grinding was less than 90%, the mechanical strength of the synthesized resin was also significantly better than that of the 001×4 synthesized by the conventional white ball process in Comparative Example 7.
[0085] Comparative Example 7 Preparation of 001×4 white balls of gel resin by traditional process: 1000mL pure water, 100g sodium chloride, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (content 0.1%) are added to a 2000mL three-necked flask and stirred evenly to form the water phase. 468.3g styrene, 31.7g divinylbenzene (content 63.0%), and 2.0g dibenzyl trithiocarbonate are mixed evenly in a beaker, and 4.0g benzoyl peroxide is added and stirred evenly to form the oil phase. Both styrene and divinylbenzene have been freed from polymerization inhibitors. Pour the mixed oil phase into the water phase, let it stand, turn on the stirring and adjust the speed, and adjust the oil droplet size within the required range. Start heating, and when the temperature rises to about 80°C, keep warm for 3h, at which time polymerization heat is released. Continue to heat up to about 90°C and keep warm for 3h. Continue to heat up to 98°C and keep warm for 6h. After the reaction is completed, wait until the temperature drops to room temperature, wash the white balls with water and dry them for later use.
[0086] The preparation of gel cation exchange resin was carried out with reference to Example 1.1, and the resin indexes were as follows: sodium type exchange capacity 4.62mmol / gd, water content 57.28%, ball rate after grinding 90.2%, ball rate after infiltration grinding 31.2%, and ball rate after enhanced infiltration grinding 14.2%. The ball rate after grinding, ball rate after infiltration grinding, and ball rate after enhanced infiltration grinding of the resin were significantly lower than those of the 001×4 gel cation exchange resin prepared in Example 7.
[0087] Example 8 Preparation of photo-initiated high-strength gel white balls: 1000mL pure water, 30g sodium chloride, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, 1.0mL methylene blue (content 0.1%) were added to a 2000mL autoclave and stirred evenly to form the water phase. 450g styrene, 55.6g divinylbenzene (mass content 63.0%), and 1.5g dibenzyl trithiocarbonate were mixed evenly in a beaker to form the oil phase; wherein styrene and divinylbenzene have been freed from the inhibitor. The mixed oil phase was poured into the water phase, allowed to stand, and the stirring was turned on to adjust the speed to adjust the oil droplet size within the required range. Under stirring, vacuum was evacuated until the pressure in the autoclave was lower than -0.06MPa, nitrogen was charged to 0.1MPa, and nitrogen was emptied to near normal pressure, and vacuum was evacuated and nitrogen was charged and discharged twice. After the last charge of 0.1MPa nitrogen, it was stored in the reactor. Then start heating. During the heating process, the heating rate is not less than 3℃ / 10 minutes. When the temperature rises to 60℃, turn on the ultraviolet lamp initiator and continue to heat up to about 70℃. Start to release polymerization heat. Continue to heat up to about 80℃. A large amount of polymerization heat is released and the temperature rises rapidly. At this time, the heating power supply can be turned off. The kettle temperature continues to rise to 120℃. The pressure in the kettle is 0.4MPa. Since the polymerization reaction starts early, the maximum temperature and pressure of the polymerization heat are lower than those without the ultraviolet lamp initiator. When the kettle temperature stabilizes or starts to drop, turn on the heating power supply and keep the reaction at 120℃ for 6h. After the reaction, wait for the temperature to drop to room temperature, wash the gel white ball with water and dry it for use.
[0088] The preparation method of the gel cation exchange resin is the same as that of Example 1.1, except that the gel white balls prepared in this example are used to replace the gel white balls in Example 1. The indexes of the prepared gel cation exchange resin are as follows: sodium type exchange capacity 4.57 mmol / gd, water content 48.83%, ball rate after grinding 98%, ball rate after osmotic grinding 97.6%, and ball rate after enhanced osmotic grinding 93.2%.
[0089] The preparation method of the gel anion exchange resin is the same as that of Example 1.2, except that the gel white balls prepared in this example are used to replace the gel white balls in Example 1. The indexes of the prepared gel anion exchange resin are as follows: Resin index: chloride type exchange capacity 3.78mmol / gd, water content 46.69%, ball rate after grinding 98%, ball rate after osmotic grinding 98%, and ball rate after enhanced osmotic grinding 94%.
[0090] The resin samples prepared in this embodiment have good mechanical strength and the ball rate of enhanced infiltration grinding is above 90%. After the ultraviolet lamp initiator is turned on, the polymerization initiation temperature is advanced, the polymerization heat release time is prolonged, the maximum temperature of the polymerization reaction is reduced, and the pressure in the kettle is controlled not to exceed 0.6MPa.
[0091] Example 9 Preparation of photo-initiated high-strength macroporous white balls: Add 1000mL pure water, 40g sodium chloride, 8g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (content 0.1%) to a 2000mL autoclave, stir evenly, and heat to 60°C to obtain a water phase for use. Add 72g solid wax to 72g liquid wax, heat to 80°C, stir evenly, and fully dissolve. Mix 318.5g styrene, 34.3g divinylbenzene (content 63.0%), 7.2g TAIC, and 0.6g benzyl dithiobenzoate in a beaker, add to the porogen composed of the above solid wax and liquid wax, stir evenly at 60°C to form an oil phase. Styrene and divinylbenzene have been freed from inhibitors. Add the mixed oil phase to the water phase, let it stand, turn on the stirring and adjust the speed to adjust the oil droplet size within the required range. Under stirring, vacuumize until the pressure in the kettle is lower than -0.06MPa, fill with nitrogen to 0.1MPa, exhaust nitrogen to near normal pressure, and then vacuumize and fill with nitrogen and exhaust nitrogen twice. After the last filling with 0.1MPa nitrogen, it is stored in the reactor. The kettle temperature is about 60°C, the ultraviolet lamp initiator is turned on, and the temperature reaction begins. When the temperature rises to about 70°C, polymerization heat begins to be generated. Continue to heat up to about 80°C, and the heat release rate is accelerated. During the heating process, the heating rate is kept not less than 2°C / 10 minutes, and the insulation operation at a constant temperature is not performed. After the kettle temperature continues to rise to 120°C, the pressure in the kettle is about 0.3MPa, and the reaction is kept at 120°C for 6h. After the reaction is completed, wait until the temperature drops to room temperature, wash the white balls with water and then dry them. Extract according to the method of Example 4, extract with toluene 6 times, boil the balls, wash them with water, and dry the macroporous white balls.
[0092] Turning on the ultraviolet lamp initiator can ensure that the polymerization reaction is carried out within a predetermined temperature range, avoiding problems such as the reaction initiation temperature being too high, the maximum reaction temperature being too high, and the kettle pressure exceeding the set value.
[0093] According to the method of Example 5, a macroporous weakly basic anion exchange resin was prepared, and only the macroporous white balls prepared in this example were used to replace the macroporous white balls prepared in Example 5. The performance indicators of the obtained resin were as follows: exchange capacity 4.92mmol / gd, water content 57.24%, infiltration grinding ball rate 99%, and enhanced infiltration grinding ball rate 98.1%. The resin indicators met the requirements of DL / T519-2004, the enhanced infiltration grinding ball rate was also high, and the mechanical strength indicators were all very good.
[0094] Example 10 Preparation of photo-initiated macroporous adsorption resin: 1000mL pure water, 60g sodium chloride, 8g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, 1.0mL methylene blue (content 0.1%) were added to a 2000mL autoclave and stirred evenly to form an aqueous phase. 168g 81.3% divinylbenzene was added to 336g toluene and stirred evenly to form an oil phase. The oil phase was added to the aqueous phase, allowed to stand, stirring was turned on to adjust the speed, and the oil droplet size was adjusted to within the required range. Under stirring, vacuum was evacuated until the pressure in the autoclave was lower than -0.06MPa, nitrogen was filled to 0.1MPa, and nitrogen was emptied to near normal pressure, and vacuum was evacuated and nitrogen was filled and emptied twice. After the last filling of 0.1MPa nitrogen, it was kept in the reactor. Then the ultraviolet lamp initiator was turned on to start the temperature reaction. When the temperature rose to 80°C, polymerization heat began to be generated. The temperature continued to rise to about 90°C, and the heat release rate was accelerated. During the heating process, the heating rate is maintained at no less than 3°C / 10 minutes, and no constant temperature insulation operation is performed. After continuing to heat to 150°C, the pressure in the kettle is about 0.6MPa, and the reaction is kept at 150°C for 3 hours. After the reaction is completed, the temperature is lowered, and the white ball is transferred to the extraction column. Water vapor at about 110°C is passed through to distill and recover toluene. After no toluene flows out, continue to pass steam for about 2 hours to completely remove the residual toluene. Cool down, wash with water, add methanol to soak for 2 hours, and filter to recover methanol. Wash with a large amount of water to remove the residual methanol to obtain a macroporous adsorption resin. The resin performance indicators are tested as follows: specific surface area 910.6m 2 / gd (square meters / g. dry resin), water content 59.37%, ball rate after grinding 95.1%, enhanced infiltration grinding ball rate 90.9%.
[0095] In Examples 8, 9, and 10, the ultraviolet lamp initiator is turned on to ensure the adjustability and controllability of the polymerization reaction, and to provide a guarantee for the stable and safe production of the polymerization white balls while ensuring the quality of the white balls.
[0096] Embodiment 11 Preparation of high-strength gel white balls: Add 1000mL pure water, 30g sodium chloride, 6g polyvinyl alcohol, 1.0g sodium carboxymethyl cellulose, and 1.0mL methylene blue (content 0.1%) to a 2000mL autoclave and stir evenly to form the water phase. Mix 450g styrene and 55.6g divinylbenzene (content 63.0%) in a beaker to form the oil phase; both styrene and divinylbenzene have been freed from inhibitors. Pour the mixed oil phase into the water phase, let it stand, turn on the stirring and adjust the speed to adjust the oil droplet size within the required range. Vacuum the autoclave until the pressure is lower than -0.06MPa under stirring, fill with nitrogen to 0.1MPa, exhaust the nitrogen to near normal pressure, and then perform two more vacuuming and nitrogen filling and exhaust operations. After the last filling of 0.1MPa nitrogen, it is stored in the reactor. Then, the temperature is raised to react. During the heating process, the heating rate is not less than 2°C / 10 minutes. When the temperature rises to about 80°C, polymerization heat begins to be generated. The temperature continues to rise to about 90°C, a large amount of polymerization heat is released, and the temperature rises rapidly. At this time, the heating power is turned off, and the kettle temperature continues to rise. The maximum temperature can reach 150°C, and the pressure in the kettle is about 0.6MPa. When the kettle temperature stabilizes or begins to drop, the heating power is turned on, and the reaction is kept at 120°C for 6 hours. After the reaction is completed, wait for the temperature to drop to room temperature, wash the gel white balls with water, and then dry them for use.
[0097] Preparation of gel strong acid cation exchange resin: The gel white balls prepared in Example 11 were used to prepare gel strong acid cation exchange resin, and the reaction process was similar to that in Example 1.1. Resin indicators: sodium type exchange capacity 4.53 mmol / gd, water content 48.91%, ball rate after grinding 98%, ball rate after infiltration grinding 96%, and ball rate after enhanced infiltration grinding 91%.
[0098] In Example 11, no RAFT chain transfer agent was added, and the maximum temperature of the polymerization reaction was higher. The corresponding polymerization kettle was also under a larger pressure, close to 0.6 MPa. That is, without adding RAFT, the reaction was more violent and the reaction speed was faster. The strength indicators of the synthesized resin, such as the grinding ball rate and the enhanced grinding ball rate, were lower than those in Example 1, but were still above 90%.
[0099] It can be seen from the results of the above examples that the resin prepared by the present invention can reach a ball rate of more than 90% by enhanced infiltration grinding, and the resin breakage rate during use is significantly reduced, which greatly prolongs the service life of the resin. Other indicators of the resin, such as exchange capacity, water content, adsorption capacity, etc., meet the requirements of DL / T519-2004 standard and relevant national standards, and are equivalent to the indicators of traditional processes.
Claims
1. A method for preparing a high-strength resin, characterized in that: The following steps are involved: S1, dissolving a dispersant in water to obtain an aqueous phase; preparing an oil phase with a polymerizable monomer, a RAFT chain transfer agent, and a porogen; wherein the mass of the RAFT chain transfer agent is 0-0.8% of the mass of the polymerizable monomer; the polymerizable monomer is styrene and divinylbenzene, and the mass of the porogen is 0-1.5 times the mass of the polymerizable monomer; or, the polymerizable monomer is divinylbenzene, and the mass of the porogen is 1-2 times the mass of the polymerizable monomer; S2, stirring and mixing the oil phase and the water phase in a reaction container, sealing, evacuating the reaction container under stirring conditions, and then filling the reaction container with nitrogen to a pressure of 0.05-0.15 MPa; heating to a temperature of 105-150° C. and a pressure of 0.3-0.6 MPa, and performing a polymerization reaction to obtain white balls; wherein, when a porogen is added to the oil phase, the porogen in the white balls is removed; S3, when the polymerization monomers are styrene and divinylbenzene, the obtained white balls are prepared into ion exchange resins; when the polymerization monomer is divinylbenzene, the obtained white balls are prepared into adsorption resins.
2. The method for preparing a high-strength resin according to claim 1, characterized in that: In S1, sodium chloride is also added to the aqueous phase.
3. The method for preparing a high-strength resin according to claim 1, characterized in that: In S1, the water is deionized water.
4. The method for preparing a high-strength resin according to claim 1, characterized in that: In S1, methylene blue is also added to the aqueous phase.
5. The method for preparing a high-strength resin according to claim 1, characterized in that: In S1, a cross-linking agent is also added to the oil phase.
6. The method for preparing a high-strength resin according to claim 1, characterized in that: In S2, the reaction container is evacuated under the stirring condition, and then nitrogen is filled into the reaction container to a pressure of 0.05-0.15 MPa. Specifically, the reaction container is evacuated under the stirring condition to a pressure lower than -0.06 MPa, and then nitrogen is filled into the reaction container to a pressure of 0.05-0.15 MPa, and the nitrogen is evacuated to normal pressure. This operation is repeated at least twice, and after the nitrogen is filled for the last time to a pressure of 0.05-0.15 MPa, the temperature is increased.
7. The method for preparing a high-strength resin according to claim 1, characterized in that: In S2, nitrogen is filled to a pressure of 0.05-0.15 MPa, and then the interior of the reaction container is irradiated with ultraviolet light while the temperature is raised.
8. The method for preparing a high-strength resin according to claim 1, characterized in that: In S2, the temperature is raised to 120-150°C.
9. The method for preparing a high-strength resin according to claim 1, characterized in that: In S3, when the polymerization monomers are styrene and divinylbenzene, the obtained white balls are prepared into ion exchange resins, specifically: the white balls are mixed with concentrated sulfuric acid and a solvent, sulfonated, and then the solvent is removed and washed to obtain a cation exchange resin; or the white balls are mixed with chloromethyl ether, swelled, and then a catalyst is added to carry out a chloromethylation reaction to obtain chlorine balls; the chlorine balls are subjected to an amination reaction with an amination agent to obtain an anion exchange resin; When the polymerization monomer is divinylbenzene, the obtained white balls are prepared into an adsorption resin, specifically, the white balls with the porogen removed are directly used as the adsorption resin.
10. A high-strength resin obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Method for removing aluminum from rare earth leachate
CN121538431A
Catalyst, preparation method thereof and method for catalytically synthesizing triacetonamine by using catalyst
CN121588901A